Métodos y técnicas de maquillaje del Carnaval de Negros y Blancos, enfocados en el Colectivo Coreográfico Danzantes del Cerrillo. (2022)
Methods and techniques of facial makeup on the Blacks and Whites Carnival will be explained in this project; The focus of this work is based on the choreographic group Cerrillo dancers who have been evidenced and collected during the EAPEAT of the Andean D 2018ance Chair 1 where explore two makeups of many exhibitions of the choreographic group. (Cumbia party in the south and Labriegos paradise). Therefore, the purpose of this work is give a evidence with the methods and techniques with a web site that i mprove to knowledge with a the different tools used by Cerrillo Dancers, those tools will be the practicality to makeup in a collective